Factors for the emission enhancement of dimidium in specific media such as in DNA and on a clay surface. Issue 41 (6th August 2019) - Nakazato, Ryosuke; Sano, Keito; Ichihara, Hiroyuki; Ishida, Tamao; Shimada, Tetsuya; Takagi, Shinsuke
Abstract : Fluorescence enhancement in DNA and on nanosheets. Abstract : Dimidium (3, 8-diamino-5-methyl-6-phenylphenanthridinium: NH2 PhP) is a well-known fluorophore as a DNA probe, although its fluorescence enhancement mechanism is not clear. In this study, we investigated the fluorescence enhancement mechanism of NH2 PhP on a clay surface by observing the fluorescence behavior. Four systematically selected phenanthridinium derivatives (PDs): NH2 PhP, 3, 8-bisdimethylamino-5-methyl-6-phenylphenanthridinium (NMe2 PhP), 5-methyl-6-phenylphenanthridinium (PhP) and 5-methylphenanthridinium (P) and synthetic clay were used as guest and host materials, respectively. It was revealed that the suppression of hydrogen bonding with water (N–HOH or NH–OH2 ) is the dominant factor for the fluorescence enhancement on the clay surface for NH2 PhP and NMe2 PhP. In addition, judging from the fluorescence enhancement for NH2 PhP, NMe2 PhP and PhP and no fluorescence enhancement for P on the clay surface, the suppression of rotation of the phenyl ring was indicated to make a partial contribution to the fluorescence enhancement mechanism. Because the fluorescence enhancement behavior was quite similar on the clay surface and in DNA, the obtained results afford an important clue to discuss the fluorescence enhancement mechanism of NH2 PhP in DNA.